New Zealand’s size and isolation can stimulate new science - Yock, Philip (New Zealand Science Review, 2016)
<span data-sheets-value="{"1":2,"2":"It is conventionally thought that New Zealand’s distance from the large, northern hemisphere centres of learning, and our relatively small population and wealth, are detrimental to the contribution we can make to the advancement of scientific knowledge. Here the reverse point of view is argued."}" data-sheets-userformat="{"2":769,"3":{"1":0},"11":4,"12":0}">It is conventionally thought that New Zealand’s distance from the large, northern hemisphere centres of learning, and our relatively small population and wealth, are detrimental to the contribution we can make to the advancement of scientific knowledge. Here the reverse point of view is argued.